Practice guidelines for outpatient parenteral antimicrobial therapy (OPAT) in Germany - Tometten, Lukas; Trost, Ulrike; Jürgens, Linda; Achterberg, Stephan; Arenz, Lukas; Audebert, Franz; Bickel, Markus; Dolff, Sebastian; Draenert, Rika; Ewering, Silke; Fischer, Julia; Friedrichs, Anette; et al. (Infection, 2025)
The practice guideline for outpatient parenteral antimicrobial therapy (OPAT) aims to encourage broader adoption of OPAT into routine clinical practice in Germany.